2018
DOI: 10.1177/2047487318789497
|View full text |Cite
|
Sign up to set email alerts
|

What constitutes the ‘Minimal Care’ interventions of the nurse, physiotherapist, dietician and psychologist in Cardiovascular Rehabilitation and secondary prevention: A position paper from the Italian Association for Cardiovascular Prevention, Rehabilitation and Epidemiology

Abstract: For the interventions, attention has been focused on conditions of major complexity requiring special care, taking into account the different care settings, the clinical conditions secondary to the disease event, and the distinct tasks of each area according to the operator's specific role. The final report performed by each professional has also been included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…Exercise intolerance, frequently manifested by fatigue or shortness of breath on minimal exertion, is a hallmark of HF 1 : one of the principal goals of treatment is to improve exercise capacity, and interventions designed to change this leading symptom in HF have been shown to improve outcomes . ETP is an important adjunct to non‐pharmacological treatment that has a proven positive effects on mortality, morbidity, exercise capacity and quality of life . Based on the analysis of 801 patients enrolled in nine randomized controlled clinical trials, the ExTraMATCH collaborative group calculated a 35% ( P < 0.05) lower risk for mortality and a 28% ( P < 0.05) lower risk for the composite endpoint of mortality or hospitalization in favour of ETP .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise intolerance, frequently manifested by fatigue or shortness of breath on minimal exertion, is a hallmark of HF 1 : one of the principal goals of treatment is to improve exercise capacity, and interventions designed to change this leading symptom in HF have been shown to improve outcomes . ETP is an important adjunct to non‐pharmacological treatment that has a proven positive effects on mortality, morbidity, exercise capacity and quality of life . Based on the analysis of 801 patients enrolled in nine randomized controlled clinical trials, the ExTraMATCH collaborative group calculated a 35% ( P < 0.05) lower risk for mortality and a 28% ( P < 0.05) lower risk for the composite endpoint of mortality or hospitalization in favour of ETP .…”
Section: Discussionmentioning
confidence: 99%
“…A variety of health care professionals have a role in HF management programmes, and because multidisciplinary teams can be costly, economic reasons might have limited the number of programme members . Finally, patient and health care professional education can differ markedly between countries/regions: in most EUR countries, no formal education exists for ETPs, with most of the applicable knowledge and skills being gained from ‘clinical experience’ and ‘training on the job’.…”
Section: Discussionmentioning
confidence: 99%
“…education, psychological support and exercise training). 16 Previously, the REACH-HF randomized controlled trial demonstrated the beneficial effect of REACH-HF intervention on quality of life with a reduction in total Minnesota Living with Heart Failure Questionnaire score by -5.7 points. Now, the cost-effectiveness of this intervention has been explored: a cost of £1721/quality-adjusted lifeyear (QALY) was demonstrated, with a 78% likelihood of being cost-effective at the willingness to pay threshold of £20,000 per QALY gained used by policymakers in UK and many developed healthcare economies.…”
Section: Left Ventricular Function In Coronary Artery Diseasementioning
confidence: 99%
“…'It takes a village to reduce cardiovascular risk!'. 1 Cardiovascular risk based on two cholesterol versions of the SCORE model within different ethnic groups Risk prediction scores try to estimate in the best possible way, combining information from various risk factors, the absolute risk that individuals free from symptomatic cardiovascular disease (CVD) will develop a cardiovascular event in the future. 2 Cardiovascular prediction models in primary care typically include predictors such as age, sex, smoking, markers of glucose intolerance, blood pressure and lipid levels.…”
mentioning
confidence: 99%